Implementasi Program Pembangunan Khatulistiwa Park Pada Kawasan Wisata Tugu Khatulistiwa Di Kota Pontianak - Imroatul Mofida; Hardilina Hardilina (JPASDEV : Journal of Public Administration and Sociology of Development, 2021)
Pontianak is the capital city of West Kalimantan, representing Indonesia with a mention Emerald Equator. The process of implementing the equatorial park development program in 2020 can’t be continued in accordance with the objectives of the development program, so that there are no more workers working on development projects. The condition of the abandoned and poorly maintained equatorial park area, such as; water does not flow in the toilet and the ablution place in the musolla. The goal to be achieved is to find out and solve problems on the factors that cause the implementation of the equatorial park development program in the equatorial monument tourist area in 2020 can’t be continued in accordance with the program's objectives, and the causes of the equatorial park area to be neglected and not maintained. This study uses a descriptive type of research with a qualitative approach. Using observation techniques, interviews, and documentation studies. The author analyzes this research using the theory of Van Meter and Van Horn in (Winarno, 2012: 158) that policy performance is influenced by six interrelated variables, namely: basic measures of policy objectives, resources, communication between organizations, characteristics of implementing organizations, economic conditions social and political, as well as the disposition of the implementor. The results of this study are the Equator Park development program is a collaboration between the Pontianak City Government and PT Mitra Bangun Kota. The two parties entered into a cooperation agreement. Technically, PT Mitra Bangun Kota is responsible for the construction of the equator park. However, in the progress of implementing the policy, there was a dispute over land ownership of the equatorial monument between the Pontianak city government and the Indonesian army. Then, it is waiting for the results of the central government's decision to swap land between the Pontianak government land and the Indonesian army. Suggestions from the results of the study are to control and pay attention to the maintenance of tourist facilities, and to empower more quality resources. Improve good communication between implementers and parties related to the implementation of further policies. Increase promotion through mass media or social media such as local TV, Facebook, Instagram, Twitter, and by using official and special accounts. This is so that information about the equator monument is conveyed to the wider community. Increasing the scope of the creative economy in the tourist area of the equatorial monument, especially the community around the potential equatorial monument tourist sites. Monitoring the implementation process of the next equatorial park revision design program so that it is more focused and in accordance with the goals and objectives of the policy.Keyword : Program Implementation, Land Ownership Disputes, Equatorial Park Development.